Dysautonomia in RFC1-related disorder: Clinical and neurophysiological evaluation. (October 2022) - Schmitt, Gabriel da Silva; Lima, Fabrício Diniz de; Matos, Paula Camila A.A.P.; Martinez, Alberto R.M.; González-Salazar, Carelis; Nucci, Anamarli; Marques, Wilson; Barsottini, Orlando Graziani P.; Pedroso, José Luiz; França, Marcondes Cavalcante
Highlights: Autonomic dysfunction involves multiple domains in RFC1-related disorder. This condition is characterized by a small fiber autonomic axonopathy. Sympathetic and parasympathetic divisions are affected in RFC1-related disorder. Abstract: Objective: To characterize and quantify autonomic involvement in patients with RFC1-related disorder of adult-onset cerebellar ataxia and idiopathic sensory neuropathy. Methods: We enrolled 16 subjects with biallelic RFC1 (AAGGG)n expansions and 16 age and sex-matched healthy controls that underwent comprehensive clinical and neurophysiological evaluation. Scales for Outcomes in Parkinson's Disease Autonomic Dysfunction (SCOPA-AUT) score was used to assess autonomic symptoms. Electrophysiological testing included assessment of heart rate variability and quantitative sudomotor axon reflex test (QSART). Between-group comparisons were assessed using non-parametric tests. Results: In the patient group, there were 9 men/7 women and the median age was 60.5 years. SCOPA-AUT scores were significantly higher in the RFC1 group compared to controls (22 vs 10, p < 0.001). Half of patients had cardiac autonomic neuropathy. In neurophysiology, there was resting tachycardia combined with abnormal responses during Valsalva maneuver and deep breathing among patients. QSART responses were also significantly reduced in the RFC1 group, especially in the lower limbs. Conclusions: Autonomic dysfunction is frequent, clinically relevant and involves multiple domains in RFC1-related disorder. Patients have both sympathetic and parasympathetic involvement. From a topographical perspective, this condition is characterized by a small fiber autonomic axonopathy. Significance: Dysautonomia is frequent, severe and related to peripheral damage in RFC1-related disorder.